"Don't gamble for money with friends": Moral‐economic types and their uses. (1st December 2020) - ZUCKERMAN, CHARLES H. P.
ABSTRACT: Some anthropologists have developed "processual" approaches to classification, arguing that we should turn our attention from reified categories to processes of categorization. A focus on how gamblers in Luang Prabang, Laos, use the categories "gambling for beer" and "gambling for money" makes clear that an adequate processual approach must disentangle two kinds of typification: one generic, one specific. People in Luang Prabang are drawn to categories of gambling as tools for both painting the world abstractly (generics) and putting action under a description (specifics). Distinguishing these two kinds of typification resolves the apparent tension between "ideal types" and messy "practice, " and it redirects the study of human classification toward understanding how people mobilize categories for diverse moral ends. [ moral economy, gifts, commodities, ideal types, typification, reflexivity, processualization, Luang Prabang, Laos ] Abstract :